Clinical case of acupuncture treatment of hemicrania continua with ophthalmic symptoms - I. V. Valueva; O. Yu. Kirgizova (Acta Biomedica Scientifica, 2022)
A clinical case of successful treatment of hemicrania continua with ophthalmic symptoms using acupuncture is presented.Chronic headache (CH) is an important medical and social problem. The fact is that CH is treated mainly medication-based. About 63 % of patients have to take analgesic and nonsteroidal anti-inflammatory drugs for a long time, while in most cases there are signs of drug overdose, which increases the risk of complications and side effects.The presented clinical case showed the acupuncture effectiveness in hemicrania continua with ophthalmic symptoms in a 23-year-old patient.Since the age of 13, the patient has been observed and repeatedly treated with complaints of persistent headaches on the left, pain in the left eye and decreased vision, accompanied by nausea, dizziness, weakness, fatigue, sleep disturbance. In 2019, against the background of constant daily intake of indomethacin, at a dosage of 9 tablets (225 mg) and a short course of glucocorticosteroids, positive dynamics of the left eye side and relative remission on the part of the pain syndrome were achieved. At the same time, choroidal ischemia with retinal edema persisted, headaches periodically occurred. Acupuncture had been performed during 6 months, 1–2 times every 14–28 days, depending on the patient’s condition, against the background of a gradual reduction in the dose of indomethacin. Complete remission has been achieved. After the end of treatment and complete withdrawal of the drug the patient has been under control for more than 3 months. The patient’s condition is satisfactory, no complaints.